2009
DOI: 10.1523/jneurosci.2536-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Wild-Type SPT1 Subunit Lowers Desoxysphingolipid Levels and Rescues the Phenotype of HSAN1

Abstract: Mutations in the SPTLC1 subunit of serine palmitoyltransferase (SPT) cause an adult-onset, hereditary sensory, and autonomic neuropathy type I (HSAN1). We previously reported that mice bearing a transgene-expressing mutant SPTLC1 (tgSPTLC1 C133W ) show a reduction in SPT activity and hyperpathia at 10 months of age. Now analyzed at a later age, we find these mice develop sensory loss with a distal small fiber neuropathy and peripheral myelinopathy. This phenotype is largely reversed when these mice are crossed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
99
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 18 publications
6
99
0
Order By: Relevance
“…Elevated DSB levels were also found in plasma of mice that are transgenic for the SPTLC1C133W mutant as reported recently (25). Interestingly, double transgenic mice, which concomitantly overexpress the C133W mutant together with wildtype SPTLC1, do not develop neurological symptoms (25).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Elevated DSB levels were also found in plasma of mice that are transgenic for the SPTLC1C133W mutant as reported recently (25). Interestingly, double transgenic mice, which concomitantly overexpress the C133W mutant together with wildtype SPTLC1, do not develop neurological symptoms (25).…”
Section: Discussionsupporting
confidence: 72%
“…However, DSB levels in the double transgenic mice are still higher than in wild-type, SPTLC1 wild type-overexpressing mice, or heterozygous SPTLC1 ϩ/Ϫ knock-out mice, suggesting that DSBs can be tolerated up to a certain threshold level. Tissue analysis revealed the presence of highly elevated DSB levels in the sciatic nerves of the C133W mice but not of wildtype mice (25). No differences in the DSB levels were seen in brain tissue of C133W and wild-type mice.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previously, we showed that the increased formation of dSLs is the pathological cause of the inherited neuropathy HSAN1 [15,31]. Clinically, HSAN1 closely resembles the diabetic peripheral neuropathy (DPN) that occurs in about 60% of diabetic patients.…”
Section: Discussionmentioning
confidence: 96%
“…13 The 1-deoxySLs were shown to be neurotoxic, blocking neurite formation in cultured neurons. 11 Herein, we report a novel HSANI mutation in SPTLC2 associated with elevated plasma 1-deoxySLs.…”
mentioning
confidence: 99%